Etiquette Vocabulary In Modern English: Social Aspect - Guzal Kabulova (Euro Asian Journal Publishing, 2024)
Language occupies a central place in our lives. According to the famous British linguist G. Widdowson, “language is acquired in the mind as abstract knowledge, but in order for this to happen, it must also be perceived in the outside world as real behavior and used as a system of signs to meet the cultural and social needs of society.” [9, р. 13-14]. This implies an approach to understanding language as a socially motivated system of signs.
Keywords: language; socially; cultural